Revealing The Influence of English Curriculum, Verbal Ability and Self-Efficacy Toward English Proficiency in Senior High School (Study on Senior High School Students in Bandung) - Witzir Sumadisastro; Dinn Wahyudin (West Science Social and Humanities Studies, 2024)
This quantitative study examines the influence of self-efficacy, verbal ability, and the English curriculum on English language proficiency among senior high school students. The research involved 96 respondents who completed questionnaires designed to measure their self-efficacy, verbal ability, perceptions of the English curriculum, and their English language proficiency levels. The data collected were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) version 4.0 to determine the relationships among the variables. The analysis revealed that self-efficacy, often considered a crucial factor in academic performance, does not significantly impact English language proficiency in this context. This finding suggests that students' beliefs in their own capabilities to learn English might not directly translate into improved language skills. On the other hand, verbal ability was found to have a significant positive influence on English language proficiency. This indicates that students with higher verbal skills tend to perform better in English, highlighting the importance of enhancing these abilities through targeted instructional strategies. Moreover, the English curriculum also showed a significant positive effect on language proficiency. A well-structured curriculum that effectively integrates language learning objectives with practical applications appears to be a key determinant of students' success in mastering English. These results underscore the importance of curriculum development and verbal ability enhancement in educational practices. In conclusion, the study provides valuable insights into the factors that contribute to English language proficiency among senior high school students. While self-efficacy alone may not be a decisive factor, the significant roles of verbal ability and curriculum quality suggest that educational stakeholders should prioritize these areas to foster better English language outcomes. Future research could explore additional variables and longitudinal effects to further understand the dynamics of language learning in educational settings.